Kung slår dam: våldsforskningsmetodologi i ett våldsamt jämställt Sverige (Sociologisk Forskning, 2010)
King captures queen. Methodology in research on violence in violently equal SwedenResearch and debate on violence against women in a Swedish context is here discussed from a perspective that focuses on the different understandings and epistemological claims behind existing positions. I crystallize a dominant perspective on violence, centred around fragmentation/deviance, and a challenging feminist understanding, centred around coherence/normality. I relate these understandings to a wider set of methodological choices and epistemological claims within research on violence against women, captured in what I call a discourse on partner violence (fragmentation) and a feminist discourse on men’s violence against women (coherence).The article also examines the reactions, in media and academic life, that a quantitative study on men’s violence against women in Sweden provoked, Captured queen, men’s violence against women in equal Sweden. A prevalence study (Lundgren et al 2001). By applying a coherent methodological approach, stemming from the feminist discourse on violence against women, the study seems to have placed itself outside what was comprehensible for many voices in the debate (from media and the academic field). I discuss the hostile reactions the study aroused, in relation to its methodology and the above presented conflicting understandings that occupy the research field “violence against women”.
Keywords: violence against women; Captured Queen; feminist theory; coherent perspective